Development of AIR (Auditory, Intellectually, Repetition)- Based Ethnomathematics E-Modules to Improve Numeracy Literacy - Inayah Fatmasari; Siska Andriani; Novian Riskiana Dewi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The numeracy literacy skills of Indonesian students remain relatively low, particularly in the geometry topics of two-dimensional shapes. One contributing factor is the limited availability of teaching materials that are relevant to local culture, as well as the lack of learning models that actively engage students. This study aims to develop an ethnomathematics-based mathematics e-module using the Auditory, Intellectually, Repetition (AIR) model to enhance students’ numeracy literacy. The research employed a Research and Development (R&D) design with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were seventh-grade students of SMP Negeri 3 Belitang Mulya and MTs Al Ihsan Kalirejo. The instruments used included expert validation questionnaires, student response questionnaires, and pretest–posttest assessments. The material expert validation produced an average score of 3.64 (very valid), and the media expert validation produced an average score of 3.84 (very valid). Student responses in both small- and large-group trials indicated a very attractive category, with average scores above 3.45. The effectiveness test showed an effect size of 0.81 (high category). These findings indicate that the ethnomathematics-based e-module using the AIR model is feasible, appealing, and effective for improving students’ numeracy literacy. This research provides an innovative teaching material alternative that is culturally relevant and can serve as a reference for developing more contextual mathematics learning.